Analysis of Soil Fertility Status and Capability Based on Slope and Land Use - Wahyu Riska Putri Ardila; Purwadi Purwadi; Fitri Wijayanti (The University of Lampung, 2026)
Declining soil fertility can be a major factor affecting soil productivity. Declining soil fertility can be caused by two factors, namely natural factors such as topography, and man made factors, such as land management. Assessment of soil fertility status is very important understand good soil fertility conditions that support agricultural and plantation activities. This study aims to determine the soil fertility status and the classification of soil fertility capability. This research was conducted through field survey on four land use units (LUUs) with 16 sampling points determined purposively. The obtained data were then combined to classify the level of status and ability of soil fertility using Fertility Capability Classification (FCC) method. The results showed that the overall LUUs have low fertility status criteria with base saturation (BS) as a heavy limiting factor, and potassium (K) and C-organic content as medium limiting factors. All LUUs, however, revealed almost the same FCC unit. Based on the FCC unit, soil fertility is constrained by some sandy texture soil types (S), with modifiers of acid soil reaction conditions (h), steep slopes (%), and some are constrained by low potassium (k).